Power and succession in Arab monarchies : a reference guide - Kechichian, Joseph A. (Lynne Rienner Publishers, 2008)
Based on scarce source material and a wide range of inside information, this exhaustive reference traces the rise of each ruling family, outlines key constitutional developments, provides details on current rulers and their approaches to succession, discusses potential contenders to power. Appendixes supply a chronological list of rulers for each monarchy, as well as the text of decrees, private letters, and constitutional provisions related to succession.